Real wage rigidities, fiscal policy, and the stability of EMU in the transition phase - Norbert Berthold (Bayerische Julius-Maximilians-Universität Würzburg, Lehrstuhl für Volkswirtschaftslehre, Wirtschaftsordnung und Sozialpolitik, 1998)
Real Wage Rigidities, Fiscal Policy, and the Stability of EMU in the Transition Phase. - EMU will start with eleven member countries as scheduled on January 1, 1999. The paper shows that the primacy of politics over economics in this decision could have serious consequences concerning the stability of EMU in the transition phase. Speculative attacks against currencies which are in economic distress due to asymmetric shocks can still happen. A speculative attack as such cannot force a country out of EMU. However, the country concerned might voluntarily decide to leave the system as the costs of staying inside EMU, e.g. due to further rising unemployment, become too large to bear.
Keywords: E24; E63; H30; J30; 330; European Monetary Union; real wage rigidity; fiscal policy; unemployment; labor market reforms; monetary policy; asymmetric shocks.; Europäische Wirtschafts- und Währungsunion; Wirtschaftliche Anpassung; Schock; Lohnrigidität; Globalsteuerung; Devisenspekulation; EU-Staaten